Personalized Indirect Calorimeter for Energy Expenditure (EE) Measurement - Francis Tsow; Erica Forzani; Nongjian Tao; Xiaojun Xian; Ashley Quach; Devon Bridgeman (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2015)
Background and aims: A personal indirect calorimeter allows everyone to assess resting and non-resting energy expenditure, thus enabling accurate determination of a person's total calorie need for weight management and fitness. The aim of this study is to compare the performance of a new personal metabolic rate tracker based on indirect calorimetry, Breezing®, with the Douglas bag method, the gold standard method for energy expenditure (EE) measurement. Methods: Energy expenditures (EE) at rest and during activities, and respiratory quotient (RQ) were measured for 12 healthy subjects, including 7 male and 5 female under different living conditions. A total of 314 measurements were performed with Breezing®, and the results were compared with those by the Douglas bag method. Results: R-squared correlation coefficients (R2) between the data obtained with Breezing® and the Douglas bag method were 0.9976, 0.9986, 0.9981, and 0.9980, for VO2, VCO2, EE, and RQ respectively. Conclusions: The EE and RQ values determined by Breezing® are in good agreement with those by the Douglas bag method.